Biogas Filter - Saeed, Adham; Sarabtta, Tamer; Abu Zahra, Bilal (My University, 2017)
The amount of biomass waste is rabidly increasing worldwide. Besides, the energy demand is also increasing. Utilities biomass for production of biogas is one of the most promising methods for producing energy renewable resource. This project aims at investigating yield and composition of produced biogas produced from anaerobic digestion for single feed stock (cow manure(. This work presents an experimental study of purification of a biogas by removal of its hydrogen sulphide (H2S), Ammonia (NH3), Siloxanes(VOCs), methane(CH4) contents by using filter.
Keywords: Biogas Filter